2012
DOI: 10.1155/2012/376470
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatics Resource for TWEAK-Fn14 Signaling Pathway

Abstract: TNF-related weak inducer of apoptosis (TWEAK) is a new member of the TNF superfamily. It signals through TNFRSF12A, commonly known as Fn14. The TWEAK-Fn14 interaction regulates cellular activities including proliferation, migration, differentiation, apoptosis, angiogenesis, tissue remodeling and inflammation. Although TWEAK has been reported to be associated with autoimmune diseases, cancers, stroke, and kidney-related disorders, the downstream molecular events of TWEAK-Fn14 signaling are yet not available in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 78 publications
0
31
0
Order By: Relevance
“…TNFRSF12A was up-regulated by loading both days. It is a cell surface receptor and thought to be a major physiologic mediator of tissue repair after acute injury by regulating inflammation, tissue remodeling, migration, differentiation, apoptosis and angiogenesis (4,9). Interestingly, TNFRSF12A specifically promotes proliferation and increases collagen production in fibroblasts (9).…”
Section: Genes Regulated Both Days Might Affect Inflammation Extracementioning
confidence: 99%
“…TNFRSF12A was up-regulated by loading both days. It is a cell surface receptor and thought to be a major physiologic mediator of tissue repair after acute injury by regulating inflammation, tissue remodeling, migration, differentiation, apoptosis and angiogenesis (4,9). Interestingly, TNFRSF12A specifically promotes proliferation and increases collagen production in fibroblasts (9).…”
Section: Genes Regulated Both Days Might Affect Inflammation Extracementioning
confidence: 99%
“…We screened published research articles related to TIE2 signaling. NetPath criteria described earlier [ 47 , 48 ] were followed for the annotation of protein-protein interactions (PPIs), enzyme-substrate relationships, and posttranslational modifications (PTMs) (catalytic events). Activation/inhibition status of proteins, alterations in protein localization, and also genes regulated at mRNA level by TIE2 signaling were also documented.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have confirmed the therapeutic potential of this pathway in human esophageal and pancreatic cancers (21), autoimmune disorders (22), muscle atrophy and injury (23), and chemokinedependent inflammatory kidney disease (24). The ever increasing knowledge and data on various downstream reactions stimulated by TWEAK-Fn14 interaction has recently been compiled into a complete repository (25). This paves the way for identification of yet unknown components of the signaling pathways.…”
Section: Tweakmentioning
confidence: 98%